Pre-Clinical Studies of Inactivated Polyvalent HFRS Vaccine - Dzagurova, Tamara K.; Siniugina, Alexandra A.; Ishmukhametov, Aidar A.; Egorova, Maria S.; Kurashova, Svetlana S.; Balovneva, Maria V.; Deviatkin, Andrey A.; Tkachenko, Petr E.; Leonovich, Oksana A.; Tkachenko, Evgeny A. (Frontiers in Cellular and Infection Microbiology, 2020)
Hemorrhagic fever with renal syndrome (HFRS) is the most common natural focal disease in the Russian Federation with about 6–12 thousand cases annually. 97.7% of all HFRS cases in Russia are caused by the Puumala virus, 1.5%—by the Hantaan, Amur, Seoul viruses, and about 0.8% by the Kurkino and Sochi viruses. There are no licensed vaccines for the prevention of HFRS in the European Region; there are no specific therapeutic to treat orthohantavirus infections. Here we report the results of candidate polyvalent HFRS vaccine preclinical studies. The vaccine was produced on the basis of three viruses: Puumala, strain PUU-TKD/VERO, Hantaan, strain HTN-P88/VERO, and Sochi, strain DOB-SOCHI/VERO. These viruses were inactivated with β-propiolacton, purified by gel filtration and aluminum hydroxide adsorbed. 18–20 g female BALB/c mice were immunized intramuscularly 2 or 3 times with a 2-week intervals and blood was taken 2 weeks after immunization. FRNT50 performed for virus specific antibodies determination. ELISA kits (Bender MedSystems, Cusabio) were used for detection of cytokines IL-1β, IL-12, INF-ɣ. Neutralizing antibodies geometric mean titers to the Puumala, Hantaan, and Sochi viruses were: 9.22 ± 0.31, 9.17 ± 0.26, 8.96 ± 0.34 log2/ml. Up to 1/32 vaccine dilution neutralizing antibodies were identified in 10/10 immunized mice with titers ≥ 3,32 log2/ml. IL-12 and INF-ɣ increased after immunization in average 5.5 and 2.8 times respectively, that reflects the Th1 type immunity stimulation. IL-1β slightly increased, that may suggest vaccine low reactogenicity. According to our preclinical investigations, the candidate polyvalent HFRS vaccine elicits balanced immune response to the Puumala, Hantaan and Sochi viruses.